Acid-Catalyzed [4+1]-Dearomatization Spiroannulation of Hydroquinones and Naphthols - Ding, Nan; Li, Zhi (Synlett, 2023)
Acid-catalyzed [4+1]-dearomatization spiroannulation reactions of electron-rich hydroquinone and naphthol derivatives were demonstrated as convenient methods to access spirocyclic cyclohexadienone derivatives. The Lewis acid Bi(OTf)3 exhibited the best catalytic performance when a 1,2-dialkynylbenzene was used as the electrophile for the spiroannulation, whereas the Brønsted acid benzene-1,2-disulfonic acid was the best catalyst when 2-ethynylbenzylic esters were used as electrophiles. Most of the reaction conditions are mild, efficient, and simple to operate.
Keywords: acid catalysis; dearomatization; spiroannulation; hydroquinones; naphthols; diyne